2019
DOI: 10.1002/hec.3917
|View full text |Cite
|
Sign up to set email alerts
|

Causes of regional variation in Dutch healthcare expenditures: Evidence from movers

Abstract: Summary We assess the relative importance of demand and supply factors as determinants of regional variation in healthcare expenditures in the Netherlands. Our empirical approach follows individuals who migrate between regions. We use individual data on annual healthcare expenditures for the entire Dutch population between the years 2006 and 2013. Regional variation in healthcare expenditures is mostly driven by demand factors, with an estimated share of around 70%. The relative importance of different causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Kalemli-Ozcan et al (2020) talk about how European countries faced with the 2008 financial crisis cut off their budgetary allocation to the health sector. The common characteristic from the studies referenced is the heterogeneity and the changing impacts among the healthcare expenditure and the resultant impact in different countries as told by Moura et al (2019). Besides, the actual challenge is the coordination and accountable handling of health care expenses due to the pandemic occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Kalemli-Ozcan et al (2020) talk about how European countries faced with the 2008 financial crisis cut off their budgetary allocation to the health sector. The common characteristic from the studies referenced is the heterogeneity and the changing impacts among the healthcare expenditure and the resultant impact in different countries as told by Moura et al (2019). Besides, the actual challenge is the coordination and accountable handling of health care expenses due to the pandemic occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while driven by socio-economic factors, urbanisation can in the short term make the health gap deeper between rural and urban areas, leading to geographical variation in health care expenditure. Previous research from the USA and the Netherlands has already shown that demand-side factors explain a large share of the variation in health care spending and utilisation across regions (Finkelstein et al 2016 ; Moura et al 2019 ). Studying the patterns of migration according to health enables us to better understand drivers of health differences across regions.…”
Section: Discussionmentioning
confidence: 99%
“…We already know that there is important variation in the health status of individuals and healthcare expenditure across regions within countries (Smyth 2008 ; Skinner 2011 ). Furthermore, evidence shows that migration and demand-side factors are important for understanding these geographical differences (Moura et al 2019 ). However, there are also contradictory findings on the associations between health and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…However, a move might also go along with a change in healthcare supplier (we were not able to study this with our data). Therefore, others have used populations of (far distance) movers to disentangle the supply effect on healthcare expenditures from the demand effect (Finkelstein, Gentzkow, and Williams 2016;Moura et al 2019). The aim of our study, however, was to object the demand side effect, not the supply side effect.…”
Section: Strengths and Limitationsmentioning
confidence: 97%